Basal Stem Rot Of Oil Palm Disease Development Planted On Mineral And Peat Soils And Pathogenicity Of Ganoderma - Virdiana, Ike (2024)
Oil palm (elaeis guineensis jacq.) has high economic value and contributes to the economy of many producing countries, especially indonesia and malaysia as the leading producers in the world. Oil palm is infected by ganoderma fungus causing basal stem rot (bsr) disease, a serious disease affecting oil palm productivity in indonesia and malaysia. In indonesia, a high incidence of bsr has been reported in oil palm planted in mineral and peat soils particularly in second generation plantings. The objectives of the present study were to identify ganoderma isolates associated with bsr in both mineral and peat soils, to conduct pathogenicity tests of ganoderma isolates from mineral and peat soils and to observe and monitor bsr disease development in infected areas in peat and mineral soil plantings. Sixteen ganoderma basidiocarps were successfully collected and isolated from infected oil palm in both simalungun (mineral soil) and south labuhan batu (peat soil) plantations in north sumatra, indonesia. The morphological characteristics of basidiocarps fall within the description for ganoderma boninense. In order to accurately identify the fungal isolates, dna sequencing of internal transcribed spacer (its) region was applied and 600 bp band were produced. Based on blast search, the isolates showed 99 – 100% similarity with the g. Boninense sequences deposited in the genbank. Phylogenetic analysis indicated the isolates from mineral soil and peat soil were grouped together along with g. Boninense reference which confirmed the isolates from both soil types as g. Boninense.